Modified incremental bit allocation algorithm for PowerLine communication in Smart Grids - Noreen, U.; Baig, S. (2013 1st International Conference on Communications, Signal Processing and Their Applications, 2013)
Smart Grids (SG) may be the most significant technological change in the history of electric grids, that can help curb the looming energy crisis worldwide, with intelligent generation, transmission and distribution of energy using a robust communication network. Power lines are a very promising solution for carrying data to serve as broadband access network in the context of SG, along with the wireless communication techniques. This paper investigates the design and simulation of a digital communication system optimized for Power Line Communication (PLC) in Smart Grids. For the proposed PLC transceiver, we consider Discrete Multitone (DMT) modulation based on a modified bit loading technique for the subcarriers. Our results reveal that the proposed incremental bit loading algorithm enhances data rate, and reduces computation time, as compared to the originally proposed incremental bit loading algorithm for PLC.